2005
DOI: 10.1177/016146810510701202
|View full text |Cite
|
Sign up to set email alerts
|

Getting My Education: Teen Mothers’ Experiences in School before and after Motherhood

Abstract: In this study, I have examined how teenagers who become pregnant experience school and how their beliefs about school are affected by their pregnancy and motherhood. Using a grounded theory approach, the perspectives of 9 young mothers in a teen parents’ program were analyzed to determine how these women reflected on their educational experience both before and after their pregnancy and on how having a child may have affected their self-understanding, particularly in relation to their schooling. The overarchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Again, changes may be most pronounced among young mothers. A recent qualitative study of young mothers participating in an educational program indicated that these mothers’ orientation to schooling changed over time (Zachry, 2005). Whereas before adolescent mothers saw little point in attending school, after having a child and returning to school, they believed education was critical to their future success.…”
mentioning
confidence: 99%
“…Again, changes may be most pronounced among young mothers. A recent qualitative study of young mothers participating in an educational program indicated that these mothers’ orientation to schooling changed over time (Zachry, 2005). Whereas before adolescent mothers saw little point in attending school, after having a child and returning to school, they believed education was critical to their future success.…”
mentioning
confidence: 99%
“…To put it another way, her general state is associated with her partner and their relatives that go out of their way just to help. This point can be strengthened by the fact as to how teenage mothers face a lot of challenges once they have entered motherhood while doing their student obligations at the same time (Zachry, 2005;Smith et al, 2012;Haight et al, 2009). The amount of support given to the mother will contribute to her overall convenience, the bigger the support, the greater the help.…”
Section: Teenage Pregnancy Amid Distance Learningmentioning
confidence: 99%
“…Like their peers, Latina teen mothers also disengage from school before the onset of motherhood as a result of feeling like they don’t belong in school (Zachry, 2005). However, when teachers express aesthetic care toward Latinas, there are specific gendered, classed, and racial dimensions that are ignored and contribute toward Latinas feeling even more disconnected from the education system.…”
Section: Latina Mothering Students Within Urban Schoolsmentioning
confidence: 99%